2010
DOI: 10.3109/14767058.2010.482618
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics in premature labor: a novel approach to identify patients at risk for preterm delivery

Abstract: Objective Biomarkers for preterm labor and delivery can be discovered through the analysis of the transcriptome (transcriptomics) and protein composition (proteomics). Characterization of the global changes in low molecular weight compounds which constitute the “metabolic network” of cells (metabolome) is now possible by using a “metabolomics” approach. Metabolomic profiling has special advantages over transcriptomics and proteomics since the metabolic network is downstream from gene expression and protein syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
117
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(123 citation statements)
references
References 249 publications
3
117
1
Order By: Relevance
“…[22][23][24][25][26] Diverse analytical data such as mass spectra and chromatograms has been directly fed into RF for either discrimination or classification. RF combines many trees to form a forest for analysis.…”
mentioning
confidence: 99%
“…[22][23][24][25][26] Diverse analytical data such as mass spectra and chromatograms has been directly fed into RF for either discrimination or classification. RF combines many trees to form a forest for analysis.…”
mentioning
confidence: 99%
“…22,27,28 Among patients in PTL, biomarkers for increased risk of preterm delivery have been identified with proteomic profiling, transcriptomics, and metabolomics, both in amniotic fluid and maternal serum. 29,30 Characterization of the identified compounds has shown that different pathologic pathways are involved in PTL besides acute inflammation. 29 Benefits Amniocentesis can establish whether an intrauterine infection is present and, thus, assist the clinician in the counseling of patients, expediting delivery, initiation of guided antibiotic therapy, and alerting the neonatologist to the increased risk of an infected or compromised neonate.…”
Section: Amniocentesismentioning
confidence: 99%
“…There are a number of limitations to such analysis, with infusion mass spectrometry potentially suffering from ion suppression effects and empirical formula being tentatively matched to more than one possible biological compound. Despite these limitations, such global, unbiased analysis has been applied to many varied fields of investigation including the study of biomarkers for disorders such as cancer and Parkinson's disease (Caudle et al, 2010;Oakman et al, 2010), preterm labor (Romero et al, 2010), and environmental pollution (Santos et al, 2010). The aim of this chapter is to discuss the application of mass spectrometry to the study of metabolites in a targeted manner.…”
Section: Introductionmentioning
confidence: 99%